Clinical characteristic of isolated thrombocytopenia in patients with bone marrow failure-related germline variants: a retrospective study from a single centre - Nanxi Dong; Jingjie Dong; Chuanao Xin; Peicheng Wang; Yaonan Hong; Rudan Zheng; Zexing Sun; Qi Liu; Yingying Shen; Xiawan Yang; Yiping Shen; Jianping Shen; et al. (Annals of Medicine)
Background Immune thrombocytopenia (ITP) comprises the majority of thrombocytopenia. Some patients respond poorly to first-line ITP therapy or develop pancytopenia years later. Recent studies link heterozygous germline variants in acquired aplastic anemia (AA), yet their role in isolated thrombocytopenia carrying bone marrow failure-related germline variants (ITGV-BMFs) remains unclear. While whole-exome sequencing (WES) detects these variants, its cost limits routine use. This study compares prognosis and clinical features of isolated thrombocytopenia in patients with ITGV-BMFsand those with classic ITP.Methods The clinical data of patients diagnosed with ITGV-BMFs were retrospectively analyzed and compared with those of patients with classic ITP from August 2018 to February 2024. The baseline characteristics, genomic systematically background, previous treatment response as well as their follow-up outcomes were compared.Results Patients with ITGV-BMFs demonstrated earlier onset age (p < 0.001), lower bleeding scores and CD34%, along with elevated mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and reticulocyte (RET) counts (p < 0.001). Multivariate logistic regression analysis showed that the patients with ITGV-BMFs may possess distinct characteristics, including an earlier age at onset (p = 0.014) and lower bleeding score (p = 0.048). Notably, MCV and RET showed promising performance in receiver operating characteristic (ROC) curve analysis. During the follow-up period, 57.69% (15/26) ITGV-BMFs patients were further confirmed as aplastic anemia (AA, n = 13) or myelodysplastic syndrome (MDS, n = 2), with a median progression-free survival (PFS) of 7.25 years (p < 0.0001).Conclusion ITGV-BMFs may be diagnosed early using elevated MCV and reticulocyte counts, a diagnostic approach that may lead to earlier intervention and improved prognosis.